Penerapan Aquaponik dengan Hidroponik DFT untuk Budidaya Kangkung di Desa Dolok Sagala - Mahyunis, Mahyunis; Gunawan, Hari; Raja, Pada Mulia; Winardi, Rafael Remit; Zakwan, Zakwan; Yazid, Abu; Hasibuan, Henry Budi (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2025)
This Community Service Program aims to implement an aquaponics system with DFT hydroponics in water spinach cultivation in Dolok Sagala Village, Dolok Masihul Subdistrict, Serdang Bedagai Regency. The aquaponics system combines fish farming with plant cultivation, where fish wastewater is used as a plant nutrient source. In contrast, the DFT hydroponics system allows efficient nutrient circulation. The application of this technology aims to increase agricultural productivity in limited land areas, provide sustainable farming solutions, and enhance local food security. The results of this activity show that the aquaponics and DFT hydroponic systems can significantly improve the growth of water spinach with minimal use of land and resources. Community participation in this activity also increased, reinforcing awareness of the importance of modern agricultural technology.